2010 IEEE 23rd International Symposium on Computer-Based Medical Systems (CBMS) 2010
DOI: 10.1109/cbms.2010.6042624
|View full text |Cite
|
Sign up to set email alerts
|

Assessing support requirements for multidisciplinary team meetings

Abstract: This paper profiles multidisciplinary team activity (MDT) in a typical teaching hospital setting and reports on a survey conducted among the teams to establish the information needs and constraints which affect their interaction. Support for pre-meeting work and post-meeting responsibilities is considered important in enabling the interaction at team meetings to be effective. Acoustics in the meeting room have higher priority over visual displays, although both 'hearing the discussion' and 'seeing images and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Assessing support requirements has been one of our main objectives, and the problem of enhancing specialist collaboration within the constraints imposed by the busy hospital setting [23]. In our earlier work, record-keeping has been identified as a key concern of MDTs at this hospital [24], and it is in the context of the implementation of a record-keeping initiative that this study is undertaken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing support requirements has been one of our main objectives, and the problem of enhancing specialist collaboration within the constraints imposed by the busy hospital setting [23]. In our earlier work, record-keeping has been identified as a key concern of MDTs at this hospital [24], and it is in the context of the implementation of a record-keeping initiative that this study is undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…Record-keeping at MDT meetings is one of the identified priorities for all of the teams surveyed, (reported in [24]), and the affordances of MDT discussion records are discussed in [23]. Here we draw attention to particular items of information, listed in Table 1, that have been requested to be part of the record of an MDT discussion, and illustrate some of the complexity of the problem of record generation.…”
Section: The Problemmentioning
confidence: 99%
“…Because of specialisation and limited resources, an individual oncologist, pathologist or radiologist is likely to belong to several MDTs. Indeed, approximately 10% of the clinical staff has reported belonging to between 6 and 10 MDTs [39]. To complicate matters further, there are several highly specialised roles, such as cardio-thoracic surgery that may be appointed to more than one hospital.…”
Section: Timementioning
confidence: 99%
“…Or "what if the information you want, such as TNM staging, could be made available in the EPR, without the need for a meeting?" Staff are emphatic in their defense of co-located meetings and their importance, which are summarised in Table 3, despite complaints about busy schedules and the fact that there is 'never enough time' [4]. They also recognise that videoconferencing can link people who would not otherwise be able to be present, but say that it is much more preferable to be in physical attendance at the main venue for MDT meetings.…”
Section: Resultsmentioning
confidence: 99%
“…They like to have others' opinion explained and the opportunity to ask questions. Issues were reported that affect MDTM performance and revolve around the agenda, the meeting itself and recordkeeping, and reported fully in [4]. This paper confines itself to issues concerning record-keeping during case discussions at MDT meetings.…”
Section: Resultsmentioning
confidence: 99%